Epigenetic deregulation of Ellis Van Creveld confers robust Hedgehog signaling in adult T‐cell leukemia. Issue 9 (8th September 2014) - Takahashi, Ryutaro; Yamagishi, Makoto; Nakano, Kazumi; Yamochi, Toshiko; Yamochi, Tadanori; Fujikawa, Dai; Nakashima, Makoto; Tanaka, Yuetsu; Uchimaru, Kaoru; Utsunomiya, Atae; Watanabe, Toshiki
<x xml:space="preserve">Abstract</x> One of the hallmarks of cancer, global gene expression alteration, is closely associated with the development and malignant characteristics associated with adult T‐cell leukemia (ATL) as well as other cancers. Here, we show that aberrant overexpression of the Ellis Van Creveld (EVC) family is responsible for cellular Hedgehog (HH) activation, which provides the pro‐survival ability of ATL cells. Using microarray, quantitative RT‐PCR and immunohistochemistry we have demonstrated that EVC is significantly upregulated in ATL and human T‐cell leukemia virus type I (HTLV‐1)‐infected cells. Epigenetic marks, including histone H3 acetylation and Lys4 trimethylation, are specifically accumulated at the EVC locus in ATL samples. The HTLV‐1 Tax participates in the coordination of EVC expression in an epigenetic fashion. The treatment of shRNA targeting EVC, as well as the transcription factors for HH signaling, diminishes the HH activation and leads to apoptotic death in ATL cell lines. We also showed that a HH signaling inhibitor, GANT61, induces strong apoptosis in the established ATL cell lines and patient‐derived primary ATL cells. Therefore, our data indicate that HH activation is involved in the regulation of leukemic cell survival. The epigenetically deregulated EVC appears to play an important role for HH activation. The possible use of EVC as a specific cell marker and a novel drug target for HTLV‐1‐infected T‐cells is implicated by these findings. The HH inhibitors are suggested as drug candidates for ATL therapy. Our findings also suggest chromatin rearrangement associated with active histone markers in ATL.